PENGARUH CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PEREODE 2017 - 2020 - Rohmatillah, Nia Nur; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Taxes have an important role in supporting development in Indonesia. Tax revenue compared to other sources of revenue is one of the largest sources of revenue for the state. The purpose of this study is to analyze and examine the effect of capital intensity on tax avoidance with financial distress as an intervening variable. The population in this study are manufacturing companies in the Textile and Garment Sub-Sector listed on the Indonesia Stock Exchange for the 2017-2020 period. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that capital intensity has no significant effect on financial distress, capital intensity has no significant effect on tax avoidance, financial distress has a significant effect on tax avoidance, and capital intensity has no significant effect on tax avoidance. Tax avoidance through financial distress has a positive but not significant effect.